Pengaruh Daya Tarik Wisata dan Citra Destinasi Wisata Terhadap Kepuasan Pengunjung di Jalan Braga - Rieke Sri Rizki Asti Karini; Anisa Septiani Eka Putri (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
Braga Street is one of the tourist destinations, which is the name of the main street in the city of Bandung. The name Braga Street was famous during the Dutch East Indies era, so along this road there are still several buildings that have typical European architecture. This street has a tourist attraction and image of a tourist destination that attracts tourists. However, currently, Braga street has several problems that affect the level of satisfaction of tourists who visit. The purpose of the study was to determine the influence of tourist attraction and image of tourist destinations on visitor satisfaction on Jalan Braga. Conducted on Jalan Braga by taking 100 tourists as respondents. Using descriptive and verifiative methods with a quantitative approach. The data obtained from the questionnaire was processed using SPSS Statistic 24 for Windows software. The results show that tourist attractiveness and image of tourist destinations have a positive and significant correlation of 73.20%. Simultaneously, tourist attractiveness and image of tourist destinations have a positive and significant effect on visitor satisfaction 57.2% and the remaining 42.8% were not studied in this study,